Pengaruh E-Mobile Presensi Jatim Terhadap Kedisiplinan Dan Kinerja ASN Di Lingkungan SMK Negeri 1 Suruh Kabupaten Trenggalek - Dian Dwi Purnakaryanto; Imam Baehaki (Otonomi, 2022)
The East Java Presence E-Mobile is an online presence using a GPS location that will detect the presence of each ASN when making an online presence using smartphone media. The purpose of the study was to describe the relationship between E-Mobile Presence with the level of discipline in carrying out the duties and performance of ASN in improving their competence. The results of hypothesis testing between East Java E-Mobile Presence and ASN Discipline obtained ttable results of -0.686 < ttable 2.040 with a significance level of 0.498, it is stated that East Java E-Mobile Presence has no effect on ASN Discipline. While the results of hypothesis testing between East Java's E-Mobile Presence and ASN Performance obtained the results of ttable of 1.726 < ttable 2.040 with a significance level of 0.094 so it was stated that East Java's E-Mobile Presence had no effect on ASN performance. The results of hypothesis testing between ASN Discipline and ASN Performance showed that the t table of ASN Discipline variables on ASN Performance was -0.006 < ttable 2,040 with a significance level of 0.995, so it was stated that ASN Discipline had no effect on ASN performance.